2016
DOI: 10.1097/md.0000000000003884
|View full text |Cite|
|
Sign up to set email alerts
|

Electroacupuncture for patients with diarrhea-predominant irritable bowel syndrome or functional diarrhea

Abstract: Diarrhea-predominant irritable bowel syndrome (IBS-D) and functional diarrhea (FD) are highly prevalent, and the effectiveness of acupuncture for managing IBS-D and FD is still unknown.The aim of this study was to compare the effectiveness of electroacupuncture with loperamide.It was a prospective, randomized, parallel group controlled trial.A total of 448 participants were randomly assigned to He electroacupuncture group (n = 113), Shu-Mu electroacupuncture group (n = 111), He-Shu-Mu electroacupuncture group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…[7] Combined with the effect of electrical stimulation, it can produce different treatment effect at different acupoints by adjusting the waveform, time, frequency, and intensity parameters. [8][9][10] Studies showed that treatment with EA could improve cognitive function in patients with Alzheimer disease. [11] Our previous study suggested that preconditioning of EA could reduce the incidence the postoperative cognitive dysfunction in aged rats.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Combined with the effect of electrical stimulation, it can produce different treatment effect at different acupoints by adjusting the waveform, time, frequency, and intensity parameters. [8][9][10] Studies showed that treatment with EA could improve cognitive function in patients with Alzheimer disease. [11] Our previous study suggested that preconditioning of EA could reduce the incidence the postoperative cognitive dysfunction in aged rats.…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by Zheng et al, showed the effectiveness of electro-acupuncture for treating patients with diarrhea prominent IBS (IBS-D). The result of the study showed that electro-acupuncture was equivalent to the use of pharmaceutical Loperamide in reducing stool frequency in patients with IBS-D. Additionally, electro-acupuncture improved stool consistency, the number of days with normal defecation, and quality of life for patients [7].…”
Section: Bodymentioning
confidence: 95%
“…The currently used medical treatments can improve intestinal motility and thereby improve the patient's quality of life, but they do not improve the contraction and relaxation of intestinal muscles, and are also associated with adverse side effects . In clinical practice, acupuncture is accepted as an alternative potentially effective therapy for constipation, irritable bowel syndrome and other diseases . It is believed that specific acupoints are associated with certain regional effects .…”
Section: Introductionmentioning
confidence: 99%
“…4 In clinical practice, acupuncture is accepted as an alternative potentially effective therapy for constipation, irritable bowel syndrome and other diseases. [5][6][7] It is believed that specific acupoints are associated with certain regional effects. 8 In the case of gastrointestinal dysfunction, ST 25 (tianshu) and ST 37 (shangjuxu) are the most commonly used acupoints for treatment.…”
mentioning
confidence: 99%